Dampak Program Bantuan UMKM Pengolah dan Pemasar Hasil Perikanan Dalam Meningkatkan Produksi dan Pendapatan Dimasa Pandemi Covid-19 - Piola, Marina Paramita S.; Karim, Rusdi Abdul; Ramly, Rizka Yunika (Gorontalo Accounting Journal, 2022)
This study aims to analyze the implementation of the PUMP-P2HP assistance program in Gorontalo Province, especially the impact on increasing POKLAHSAR production and income. This research uses the Approach qualitative with case study method. The results show the implementation of this program through the facilitation of capacity and institutional strengthening by socialization, training, and mentoring. In addition, POKLAHSAR received BLM funding assistance. This research is expected to be a benchmark in implementing assistance programs for MSMEs under the auspices of the Department of Marine Affairs and Fisheries.